Towards Multifunctional Synthetic Vectors - Demeneix, Barbara; Hassani, Zahra; Behr, Jean-Paul (Current Gene Therapy, 2004)
Recent progress on the fronts of design, formulation and delivery with synthetic vectors has increased the potential of non-viral approaches to attain therapeutic applications. However, a number of hurdles remain to be cleared. On the one hand, we have the problem of producing and formulating stable, diffusible complexes and on the other hand, we have to face the fact that in vivo delivery is probably too complex and multifaceted to be achieved successfully with a single carrier molecule in most instances. This review concentrates on this latter aspect and the design of artificial multicomponent vectors aimed at providing solutions to membrane crossing, endosomal escape and navigation through the nuclear pore. In many instances the solutions proposed have been inspired by natural mechanisms exploited by bacteria and viruses. However, entirely novel chemical approaches such as monomolecular DNA condensation via detergent dimerization, or endosome disruption by osmotic swelling, are also being investigated and developed. The combination of these naturally inspired and chemically-originated approaches is bringing us continually closer to the concept of constructing an artificial virus capable of delivering viable nucleic acid-based pharmaceuticals to defined cells in vivo. This review considers the most successful current solutions to the main biological barriers to gene delivery including appropriate DNA compaction, cell targeting and entry, vacuole escape, nuclear import and in vivo delivery. In the latter section, emphasis is placed on one of the most versatile non-viral vectors currently available, linear polyethylenimine.
Keywords: polypeptide